Analysis of Buying and Selling Used Mobile Phones from the Perspective of Sharia Economic Law - Mohammad Robi Iroki Hasan (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
The development of communication technology has increased public demand for mobile phones, including used mobile phones that are more affordable than new products. This condition has encouraged the growth of used mobile phone trading in various stores, one of which is Garasi Phone Counter Jember. This study aims to determine the transaction mechanism of buying and selling used mobile phones and to analyze the practice based on Islamic economic law. This research uses an empirical qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving the store owner, employees, and consumers. The results of the study show that the buying and selling process of used mobile phones at Garasi Phone Counter Jember is carried out through product inspection, price determination, bargaining, agreement, and handover of the goods. From the perspective of Islamic economic law, the practice is generally permissible because it fulfills the pillars and conditions of sale and purchase. However, transparency regarding the condition of the mobile phones, especially refurbished products, must be clearly conveyed to avoid elements of fraud and uncertainty that may harm consumers. Therefore, honesty and transparency are essential principles in creating transactions that are in accordance with Islamic economic law.